2014
DOI: 10.1073/pnas.1320329111
|View full text |Cite
|
Sign up to set email alerts
|

Radiometric 81 Kr dating identifies 120,000-year-old ice at Taylor Glacier, Antarctica

Abstract: We present successful 81 Kr-Kr radiometric dating of ancient polar ice. Krypton was extracted from the air bubbles in four ∼350-kg polar ice samples from Taylor Glacier in the McMurdo Dry Valleys, Antarctica, and dated using Atom Trap Trace Analysis (ATTA). The 81 Kr radiometric ages agree with independent age estimates obtained from stratigraphic dating techniques with a mean absolute age offset of 6 ± 2.5 ka. Our experimental methods and sampling strategy are validated by (i) 85 Kr and 39 Ar analyses that s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 63 publications
4
90
0
Order By: Relevance
“…Finally, the very low δ 18 O atm values of −0.4 ‰ close to the glacier terminus are a clear indication of interglacial origin, in this case most likely Eemian (∼ 125 ka BP). The Eemian age of this part of the glacier has already been independently confirmed by Buizert et al (2014) using Kr-81 dating.…”
Section: Along-flow Profile Covers Entire Glacial Cyclementioning
confidence: 56%
See 3 more Smart Citations
“…Finally, the very low δ 18 O atm values of −0.4 ‰ close to the glacier terminus are a clear indication of interglacial origin, in this case most likely Eemian (∼ 125 ka BP). The Eemian age of this part of the glacier has already been independently confirmed by Buizert et al (2014) using Kr-81 dating.…”
Section: Along-flow Profile Covers Entire Glacial Cyclementioning
confidence: 56%
“…We can therefore use these data to assign ages to the different locations by comparing the gas composition to other ice cores. We restrict the age range to the last glacial cycle, a well-justified assumption given that these sites are 10+ km upstream from a site that has been dated to 120 ka BP (before present = before 1950 AD) and close to two other sites that were dated to 12 and 50 ka BP by Buizert et al (2014) using Kr-81 radioisotope dating. The gas data then suggest unique ages for cores D2 and D3, and two possible ages for D1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An along-flow transect of water stable isotopes from just below the equilibrium line to the terminus of the glacier revealed ice from the last glacial period in several sporadic intervals (Aciego et al, 2007); the sporadic nature of the occurrences was later shown to be an artifact of sampling nearly parallel to isochrones such that they were occasionally crossed (Baggenstos et al, 2017). More recent across-flow profiles dated with gases revealed ice that varies continuously in age from the Holocene to the last ice age 20 (Schilt et al, 2014;Bauska et al, 2016;Baggenstos et al, 2017), with ice of last interglacial or older age found near the terminus of the glacier (Baggenstos et al, 2017;Buizert et al, 2014). The most utilized archive to date is a 500 m section (called the 'Main Transect') oriented perpendicularly to isochrones across a syncline/anticline pair containing ice spanning ~50 ka before present (BP) to the mid Holocene (7 ka).…”
mentioning
confidence: 99%